1958
DOI: 10.1152/ajplegacy.1958.192.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gram-Negative Endotoxin on Pulmonary Circulation

Abstract: Effects of endotoxin on the pulmonary hemodynamics of dogs and cats have been studied in intact animals, open chest animals with and without control of cardiac output by an extracorporeal venous reservoir—pump system, and in isolated perfused continuously weighed lungs. Pulmonary artery pressure increased without a rise in left atrial pressure in all preparations following the injection of endotoxin. Pulmonary artery wedge and small pulmonary vein pressures uniformly increased. Total pulmonary vascular, pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
1

Year Published

1963
1963
1974
1974

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(33 citation statements)
references
References 0 publications
1
31
0
1
Order By: Relevance
“…Our initial studies confirmed earlier work (Kuida, Hinshaw, Gilbert & Visscher, 1958;Kuida, Gilbert, Hinshaw, Brunson & Visscher, 1961) which showed that an acute pulmonary vasoconstriction occurred. This resulted in pulmonary oedema and right ventricular failure and was immediately lethal in approximately half of the cats.…”
Section: Introductionsupporting
confidence: 90%
“…Our initial studies confirmed earlier work (Kuida, Hinshaw, Gilbert & Visscher, 1958;Kuida, Gilbert, Hinshaw, Brunson & Visscher, 1961) which showed that an acute pulmonary vasoconstriction occurred. This resulted in pulmonary oedema and right ventricular failure and was immediately lethal in approximately half of the cats.…”
Section: Introductionsupporting
confidence: 90%
“…Although our data do not define the mechanism responsible for differences in systemic and pulmonary vascular behavior, the possible role of serotonin release during the pyrogen reaction merits consideration (11,27). Our studies in man contrast with Kuida's demonstration of marked postcapillary pulmonary hypertension in animals (17). Aside from the possible effects of species variation and quite dissimilar experimental conditions, the differences may be attributed to the fact that the doses of pyrogen used by Kuida were massive when compared to those used in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…However, data concerning respiratory gas exchange, pulmonary hemodynamics, and arterial blood gas composition in hyperpyrexia are rather fragmentary and inconclusive (7)(8)(9)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Since the pump-perfused lobe in the present study was not dissected or excised, and was perfused with blood which recirculated through the entire body of the animal, these lobar vessels might have been more sensitive to small differences in vasoactive substances than were the excised lobes in the previous study (10). Other studies (24) have shown that the pressor responses of the separated lobar vessels in this preparation to similar quantities of serotonin were greater than those reported with that excised lobe preparation (25) (26), and injections of fibrinopeptides (27), and endotoxin (28).…”
Section: Discussionmentioning
confidence: 66%